Spin-dependent transport and functional design in organic ferromagnetic devices - Hu, Guichao; Xie, Shijie; Wang, Chuankui; Timm, Carsten (Beilstein Journal of Nanotechnology, 2017)
Organic ferromagnets are intriguing materials in that they combine ferromagnetic and organic properties. Although challenges in their synthesis still remain, the development of organic spintronics has triggered strong interest in high-performance organic ferromagnetic devices. This review first introduces our theory for spin-dependent electron transport through organic ferromagnetic devices, which combines an extended Su–Schrieffer–Heeger model with the Green’s function method. The effects of the intrinsic interactions in the organic ferromagnets, including strong electron–lattice interaction and spin–spin correlation between π-electrons and radicals, are highlighted. Several interesting functional designs of organic ferromagnetic devices are discussed, specifically the concepts of a spin filter, multi-state magnetoresistance, and spin-current rectification. The mechanism of each phenomenon is explained by transmission and orbital analysis. These works show that organic ferromagnets are promising components for spintronic devices that deserve to be designed and examined in future experiments.
Keywords: magnetoresistance; organic ferromagnet; spin-current rectification; spin filtering; transport